Readmission following both cardiac and non‐cardiac acute dyspnoea is associated with a striking risk of death. (10th June 2021) - Čerlinskaitė, Kamilė; Mebazaa, Alexandre; Cinotti, Raphaël; Matthay, Michael; Wussler, Desiree N.; Gayat, Etienne; Juknevičius, Vytautas; Kozhuharov, Nikola; Dinort, Julia; Michou, Eleni; Gualandro, Danielle M.; Palevičiūtė, Eglė; et al.
Abstract: Aims: Readmission and mortality are the most common and often combined endpoints in acute heart failure (AHF) trials, but an association between these two outcomes is poorly investigated. The aim of this study was to determine whether unplanned readmission is associated with a greater subsequent risk of death in patients with acute dyspnoea due to cardiac and non‐cardiac causes. Methods and results: Derivation cohort (1371 patients from the LEDA study) and validation cohort (1986 patients from the BASEL V study) included acute dyspnoea patients admitted to the emergency department. Cox regression analysis was used to determine the association of 6 month readmission and the risk of 1 year all‐cause mortality in AHF and non‐AHF patients and those readmitted due to cardiovascular and non‐cardiovascular causes. In the derivation cohort, 666 (49%) of patients were readmitted at 6 months and 282 (21%) died within 1 year. Six month readmission was associated with an increased 1 year mortality risk in both the derivation cohort [adjusted hazard ratio (aHR) 3.0 (95% confidence interval, CI 2.2–4.0), P < 0.001] and the validation cohort (aHR 1.8, 95% CI 1.4–2.2, P < 0.001). The significant association was similarly observed in AHF (aHR 3.2, 95% CI 2.1–4.9, P < 0.001) and other causes of acute dyspnoea (aHR 2.9, 95% CI 1.9–4.5, P < 0.001), and it did not depend on the aetiology [aHR 2.2, 95% CI 1.6–3.1 for cardiovascular readmissions; aHR 4.1, 95% CI 2.9–5.7 for non‐cardiovascular readmissions ( P < 0.001 for both)] or timing of readmission. Conclusion​s: Our study demonstrated a long‐lasting detrimental association between readmission and death in AHF and non‐AHF patients with acute dyspnoea. These patients should be considered 'vulnerable patients' that require personalized follow‐up for an extended period.